ChemInform Abstract: Dimethylammonium Tetraaqua(hydrogensulfato)sulfatocuprate(II). Issue 38 (10th September 2014) - Held, Peter
Abstract [Me2NH2] [Cu(HSO4)(SO4)(H2O)4] crystallizes from an aqueous solution of CuSO4, Me2NH, and H2SO4 in a stoichiometric ratio at 25 °C.